Islamic Community Development Based on Local Potential at the Makam of Sheikh Hasan Munadi, Nyatyono Village, Semarang Regency - Agus Riyadi (IAIN Batusangkar, 2022)
West Ungaran Subdistrict, especially Nyatyono, is a village that has local potential in the form of cultural assets with distinctive Islamic characteristics, namely the tomb of Sheikh Hasan Munadi. This study is intended to answer the following problems: 1). How is the development of an Islamic community based on local potential at the Tomb of Sheikh Hasan Munadi. 2). Is the development of an Islamic community based on local potential at the Tomb of Sheikh Hasan Munadi able to develop the condition of the community in Nyatyono village. This type of research is descriptive qualitative. As for how to collect data through observation, interviews and documentation. The results of the study show: 1 The stages of developing an Islamic community based on local potential at the Tomb of Sheikh Hasan Munadi are carried out through the following stages: a) Preparation and identification, b) Determining the priority scale, c) Determining the direction and objectives in the implementation of activities, d) Identifying resources owned by the manager, e) Formulation and implementation of the list of activities and budgeting. 2 The results of the development of an Islamic community based on local potential at the tomb of Sheikh Hasan Munadi are: a) it can improve the economy of the Nyatyono village community, b) increase the religious spiritual understanding of the Nyatyono village community, c) increase the education sector of the Nyatyono village community, 4) increase in the social field, culture and health as well as the standard of living and economy of the Nyatyono village community